Analysis of Student Ethics in the Classroom Learning Process at SDN X Minangkabau - Radika, Radika; Safrizal, Safrizal; Komalasari, Elis (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
This research is motivated by a situation where the researcher sees the phenomenon of the lack of student ethics during the learning process in the SD X Minangkabau class. The purpose of this study is to describe how the teacher's strategy in improving ethics during the learning process at SD X Minangkabau class. In this study using qualitative research methods. The informants of this study were 1 fifth grade teacher, 20 fifth grade students who were selected by purposive sampling. The instrument in this research is the researcher himself, with data collection techniques and researchers assisted by supporting instruments in the form of observation guidelines, interview guidelines and documentation studies. The data analysis technique uses data reduction, data display and conclusion stages. Data validity assurance in this study uses triagulation by combining 3 ways of collecting data. The results of this study indicate that the strategies used by teachers in improving student ethics during the learning process in class are by linking the Civics material studied with everyday life, linking the BAM material studied with everyday life, linking the Ecosystem material studied with everyday life and using learning media.